2019
DOI: 10.18517/ijaseit.9.3.9037
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Type of Solvent and Extraction Temperature of Corn Silk Extracts

Abstract: Corn silk has not been well-utilized.  Actually it has the capacity to develop into functional food because it contains bioactive compounds and high natural antioxidant such as flavonoids and phenolics and positive effects on human health. There are several factors that influence the quality of corn silks extracts, including ratio (raw:solvents) and extraction temperature. This research was couducted to determine the influence of ratio (raw:solvent) and extration temperature of corn silk extracts.  The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It means that the higher temperature in drying process will decrease the antioxidant activity [68]. The decreased activity antioxidant was also caused by different type solvent and extraction temperature [69]. Data followed by different letter in the same line showed statistically significant (p<0.05).…”
Section: Phytochemical Contentsmentioning
confidence: 90%
“…It means that the higher temperature in drying process will decrease the antioxidant activity [68]. The decreased activity antioxidant was also caused by different type solvent and extraction temperature [69]. Data followed by different letter in the same line showed statistically significant (p<0.05).…”
Section: Phytochemical Contentsmentioning
confidence: 90%
“…This is because a temperature that is too high for a prolonged period causes more water content to evaporate, decreasing the yield, and vice versa, a temperature that is too low causes less water to evaporate, producing a high yield. [6], [34]- [36].…”
Section: Fig 1 Black Mangrove Powder Extracts Contour Plot Chart and ...mentioning
confidence: 99%
“…This is done following earlier studies by [32] and [33], which found that the yield was reduced at higher temperatures and over extended periods. This is because a temperature that is too high for a prolonged period causes more water content to evaporate, decreasing yield, and that a temperature that is too low causes less water to evaporate, increasing yield [6], [34]- [36].…”
Section: Water Contentmentioning
confidence: 99%
“…The higher the temperature and the longer the time of extraction, the lower the yield obtained. This is due to too high temperatures with a long time cause more water content evaporated, resulting in yield decrease, and vice versa, the lower the temperature used, then the less water evaporated so it can obtain the high yield [28]- [31]. 2 shows that, the lowest average of water content obtained on the parameters of A4B4 (65 o C and the temperature-time 25 minutes) at 4.51%, while the highest average of water content is obtained in the A1B1 (50 o C and the temperature is 10 minutes) at 9.77%.…”
Section: Yieldmentioning
confidence: 99%